Parental smoking, maternal alcohol consumption during pregnancy and the risk of neuroblastoma in children. A pooled analysis of the ESCALE and ESTELLE French studies. Issue 11 (21st February 2019) - Rios, Paula; Bailey, Helen D.; Poulalhon, Claire; Valteau‐Couanet, Dominique; Schleiermacher, Gudrun; Bergeron, Christophe; Petit, Arnaud; Defachelles, Anne‐Sophie; Marion, Gambart; Sirvent, Nicolas; Ducassou, Stéphane; Munzer, Caroline; et al.
Abstract : Neuroblastoma (NB) is the most common extra‐cranial tumour in children. Little is known about the aetiology of NB. The early age at onset and the embryonic nature suggest a role for perinatal exposures. We conducted a pooled analysis of two French national population‐based case–control studies to explore whether there was an association between parental smoking and alcohol consumption and the risk of NB. The mothers of 357 NB cases and 1, 783 controls from general population, frequency matched by age and sex, were interviewed on demographic, socioeconomic and perinatal characteristics, maternal reproductive story, and life‐style and childhood environment. Unconditional logistic regression was used to estimate pooled odds ratios and 95% confidence intervals. A meta‐analysis of our findings with those of previous studies was also conducted. Maternal smoking during pregnancy was slightly more often reported for the cases (24.1%) than for the controls (19.7%) (OR 1.3 [95% CI 0.9–1.7]; summary OR from meta‐analysis 1.1 [95% CI 1.0–1.3]. Paternal smoking in the year before child's birth were not associated with NB as independent exposure (OR 1.1 [95% CI 0.9–1.4] but the association was stronger when both parents reported having smoked during pregnancy (OR 1.5 [95% CI 1.1–2.1]. No association was observed with maternal alcohol intake during pregnancy (OR 1.0 [95% CI 0.8–1.4], summary OR from meta‐analysis 1.0 [95% CI 0.9–1.2]. Our findings provide some evidence of an association between maternal smoking during pregnancy and NB and add another reason to recommend that women refrain from smoking during pregnancy. Abstract : What's new? Neuroblastoma strikes early in life, which suggests an influence from risk factors that occur before birth. Here, the authors looked at parental smoking and alcohol drinking in a large population sample in France. Cases were collected by a nationwide registry, so the sample was very complete, and included 357 cases of neuroblastoma. The analysis revealed no association between maternal alcohol drinking and the cancer, nor between neuroblastoma and paternal smoking. They did identify a slight positive association with maternal smoking, and the effect was stronger if both parents smoked.